Efektivitas Juru Bahasa Isyarat Khutbah di Masjid UIN Sunan Kalijaga - Mustarjudin, Mustarjudin (INKLUSI, 2017)
The center for Disability Services at UIN Sunan Kalijaga in collaboration with UIN Sunan Kalijaga Mosque provides sign interpreter service for the Deaf worshipers during the Friday sermon. This study aims to assess the effectiveness of sign language interpreters. Based on the analysis of three approaches and five measures of effectiveness, research shows that the Friday sermon interpretation program has not been effective. This is due to several factors, namely: the sitting position of the Deaf which determines the quality of visualization of sign language interpretation of khutbah material, the lack of language capability of sign language interpreters, the coordination is not done between the PLD and mosque management, the absence of material publications that facilitate the sign interpreter understand the material, lack of religious understanding of Deaf so that they ar less able to understand the sermon topic.[Pusat Layanan Difabel UIN Sunan Kalijaga Yogyakarta bekerja sama dengan Laboratorium Agama Masjid UIN Sunan Kalijaga Yogyakarta menyediakan layanan juru bahasa isyarat untuk jamaah Tuli pada saat khutbah Jumat. Penelitian ini bertujuan untuk menilai efektifitas juru bahasa isyarat. Berdasarkan analisis tiga pendekatan dan lima ukuran efektivitas, penelitian menunjukkan bahwa program juru bahasa isyarat khutbah Jumat belum dapat dikatakan efektif. Hal tersebut disebabkan beberapa faktor, yaitu: posisi duduk Tuli yang menentukan kualitas visualisasi juru bahasa isyarat materi khutbah, minimnya kemampuan bahasa juru bahasa isyarat, koordinasi yang tidak dilakukan antara pihak PLD dan pengurus masjid, tidak adanya publikasi materi yang memudahkan juru bahasa isyarat memahami materi, minimnya pemahaman keagamaan Tuli sehingga kurang dapat memahami materi khutbah.]